The developing adult - GERDES,Lily 1988 (South Africa Butterworth publishers, 1988)
The book consist of three past ,the first part lays the theoretical and research foundation deemed necessary for an understanding of adult development, second part deals with the contexts and domains within which adult development occurs ,marriage and the family ,work and leisure are discussed .Different life styles are considered ,including being single, divorced or widowed the last part far more emphasis is placed on transitions from one stage to the next .
human development ,theories of adulthood ,the psychology of men and women ,marriage and family, youth: transition to adulthood ,middle adulthood, late adulthood